Music is the rythm of life. (Journal of Parents and Teachers, 2014)
In this attractive article with illustrated vignettes explains that music accompanies us in our lives, which is a means of expression, an aesthetic emotion and a harmony of the senses.
Keywords: Music; company; aesthetic pleasure; medium of expression; senses.